2020
DOI: 10.2196/19796
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Apps on COVID-19 Launched in the Early Days of the Pandemic: Content Analysis and Review

Abstract: Background Mobile health (mHealth) app use is a major concern because of the possible dissemination of misinformation that could harm the users. Particularly, it can be difficult for health care professionals to recommend a suitable app for coronavirus disease (COVID-19) education and self-monitoring purposes. Objective This study aims to analyze and evaluate the contents as well as features of COVID-19 mobile apps. The findings are instrumental in help… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
140
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(172 citation statements)
references
References 34 publications
0
140
0
5
Order By: Relevance
“…12 Consequently, various countries have developed mobile health applications to improve the delivery of healthcare services to contain the spread of the novel coronavirus during the COVID-19 pandemic. [13][14][15][16][17][18][19][20][21] It is pertinent to point out that in general several of these studies are related to the present investigation. For example, one study indicated that more than 2 million of participants used a free smartphone-based app to report potential symptoms of COVID-19 in the United Kingdom and the USA.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…12 Consequently, various countries have developed mobile health applications to improve the delivery of healthcare services to contain the spread of the novel coronavirus during the COVID-19 pandemic. [13][14][15][16][17][18][19][20][21] It is pertinent to point out that in general several of these studies are related to the present investigation. For example, one study indicated that more than 2 million of participants used a free smartphone-based app to report potential symptoms of COVID-19 in the United Kingdom and the USA.…”
Section: Introductionmentioning
confidence: 95%
“…14 Alike, a literature review identified the COVID-19 apps accessible in Canadian application stores at the start of the pandemic. 15 Also, the apps on COVID-19 launched between April 18 and May 5, 2020 in the USA were examined by Ming et al 20 Likewise, a study investigated the COVID-19 apps used in India. 19 Furthermore, Davalbhakta et al conducted a literature review to detect the COVID-19 apps used in the United States, United Kingdom, and India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol vapor is also harmful Santos et al [ 33 ] 10 Sharing of cup, utensils, food, or drink items It transmits infection Müller et al [ 34 ] 11 Stay home The measures by which transmission can be reduced are; rules on distance and hygiene to prohibitions on meetings and extension of school and university holidays to the closure of all non-system-relevant facilities in a country in connection with the regulation of individual freedom of movement i.e. lockdown Adhikari et al [ 35 ] 12 Namaste This way of greeting avoids physical touch as observed in hand shaking Kulkarni et al [ 36 ] 13 Hugs, handshake, high five, fist bump,, & If individuals will go for these types of greetings or mode of celebration, transmission of virus will happen Adhikari et al [ 35 ] 14 COVID-19 associated app provided by the government It’s always good to upload COVID-19 app on your mobile to know latest update as well as COVID-19 positive patient in the vicinity Ming et al [ 37 , 38 ] 15 Make a note of helpline number of emergency medical facility In case if you submit the symptoms such as fever, difficulty in breathing and cough. This put stats accordingly if you are at high or low risk of getting the disease, and further in tracing and monitoring of the patient Collado-Borrell et al [ 38 ] …”
Section: Structure Of Sars-cov-2 Virusmentioning
confidence: 99%
“…The upward trend in the use of digital health consultation applications has been greatly accelerated by the current COVID-19 pandemic [1]. This has compelled general practitioners, in particular, to rapidly shift from face-to-face consultations to telephone or video interactions wherever possible [2].…”
Section: Introductionmentioning
confidence: 99%